2007
DOI: 10.1021/la701150q
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Miniemulsion Polymerization Using Laponite Clay as a Stabilizer

Abstract: Solid-stabilized, or Pickering, miniemulsion polymerizations using Laponite clay discs as stabilizer are investigated. Free radical polymerizations are carried out using a variety of hydrophobic monomers (i.e., styrene, lauryl (meth)acrylate, butyl (meth)acrylate, octyl acrylate, and 2-ethyl hexyl acrylate). Armored latexes, of which the surfaces of the particles are covered with clay discs, are obtained, as confirmed by scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). Overall polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
221
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(226 citation statements)
references
References 37 publications
2
221
0
3
Order By: Relevance
“…Bausch et al [83,84] showed that for large droplets onto which thousands of microspheres were assembled, this rule of 12 defects prevailed in the form of five-and seven-neighbor line defects, or grain boundary scars. Bon and coworkers [85] studied a system of intermediate size (tens to hundreds of particles on a sphere), i.e., the packing patterns of silica nanoparticles on polystyrene latex particles made via Pickering miniemulsion polymerization [86,87]. They found an excellent correlation between the experimental morphology and the nearest-neighbor distribution using metropolis Monte Carlo simulations, using a 12-24 Lennard-Jones potential.…”
Section: Droplets Armored With a Layer Of Adhered Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bausch et al [83,84] showed that for large droplets onto which thousands of microspheres were assembled, this rule of 12 defects prevailed in the form of five-and seven-neighbor line defects, or grain boundary scars. Bon and coworkers [85] studied a system of intermediate size (tens to hundreds of particles on a sphere), i.e., the packing patterns of silica nanoparticles on polystyrene latex particles made via Pickering miniemulsion polymerization [86,87]. They found an excellent correlation between the experimental morphology and the nearest-neighbor distribution using metropolis Monte Carlo simulations, using a 12-24 Lennard-Jones potential.…”
Section: Droplets Armored With a Layer Of Adhered Particlesmentioning
confidence: 99%
“…Bon and coworkers [87] described the Pickering miniemulsion polymerization of styrene using Laponite RD clay discs as solids stabilizer in the absence of any auxiliary comonomer or surfactant. In a detailed mechanistic study [86], they reported that this Pickering miniemulsion polymerization using Laponite clay discs (ca. 25 nm in diameter and 1 nm in height) was successful and yielded armored polymer latexes for a variety of hydrophobic monomers, including styrene, lauryl(meth)acrylate, butyl(meth)acrylate, octylacrylate, and 2 ethylhexylacrylate.…”
Section: Polymerization Of Emulsion Droplets Armored With Inorganic Nmentioning
confidence: 99%
“…So far, the preparation and forming principle of Pickering emulsion have been well documented by Binks and coworkers [15][16][17], Midmore [18], and Bon and coworkers [19,20] Moreover, a series of nanocomposite microspheres have been prepared. Bon and Colver [21] reported the fabrication of a variety of armored latex by Pickering miniemulsion polymerizations using Laponite clay discs as stabilizer. Zaragoza-Contreras et al [22] described the synthesis of carbon black/polystyrene conductive nanocomposite by Pickering suspension polymerization technique.…”
mentioning
confidence: 99%
“…Then, emulsion polymerization [111,112] can be carried out to prepare polymeric nanocomposite particles, as presented schematically in Figure 12a. SEM images of laponite clay-armored polystyrene latex particles and montmorillonite clay-armored polyacrylamide latex particles are shown as further examples in Figures 12b [111] and 12c [113], respectively.…”
Section: Polymerisation Of Hybrid Colloidal Particles With An Inorganmentioning
confidence: 99%